Analysis of Mathematical Connection Ability in terms of Mathematical Resilience and Gender of MTs Students - Alissa Az Zahra; Windia Hadi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to describe the Mathematical Connection Ability (MCA) in terms of Mathematical Resilience (MR) and gender of MTs students. The research method used is descriptive qualitative. This research was conducted in the even semester of the 2021/2022 academic year. The subjects in this study were class VIII MTs Al Musyarrofah Jakarta. The research instrument used was a MR questionnaire and MCA test questions which had been validated and declared suitable for use by 2 lecturers and mathematics teachers. The process of selecting subjects in this study used the Wright Maps table in the Winsteps application. The subjects selected were 5 people based on 3 categories of MR, namely high, medium, low from different genders. The results showed that students with high MCA and MR for female gender were better than boys, but on the other hand students with moderate MCA and MR and low gender. men are better than women. So the results of the study concluded that MR had an effect on the MCA but gender had no effect on the MCA of MTs students.